Answer:
z = 4
y = -1
x = 2
Step-by-step explanation:
x - y = 3
Therefore => x = 3 + y
y + 2z =7
Therefore => y= 7 - 2z
We have the equation :
2x + 3y + 4z = 17
2(3 + y) + 3(7 - 2z) + 4z = 17
6 + 2y + 21 - 6z +4z = 17
2(7 -2z) - 2z + 27 = 17
14 - 4z - 2z + 27 = 17
-6z + 41 = 17
-6z = -24
z = 4
Answer:
k = 4
Step-by-step explanation:
Plug in the values of 2 for x and 0 for y, and solve for k.
2x + 3y = k
2(2) + 3(0) = k
4 = k
k = 4
we have the function
Part a
For t=7
substitute in the given function
For t=14
For t=21
For t=28
For t=35
Observation: The values of E varies from -1 to 1, including the zero
Part B
Remember that
The Period goes from one peak to the next
so
Period=2pi/B
B=pi/14
Period=(2pi)/(pi/14)=2pi*14/pi=28
<h2>the period is 28 days</h2>
He will eventually make enough money to buy his car
Answer:
x = -1
Step-by-step explanation:
Step 1: Write equation
-4(-5x + 2) - 3x - 5 = -30
Step 2: Solve for <em>x</em>
<u>Distribute -4:</u> 20x - 8 - 3x - 5 = -30
<u>Combine like terms:</u> 17x - 13 = -30
<u>Add 13 on both sides:</u> 17x = -17
<u>Divide both sides by 17:</u> x = -1